2011
DOI: 10.1096/fj.11-182246
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐engineered vascular grafts form neovessels that arise from regeneration of the adjacent blood vessel

Abstract: We developed a tissue-engineered vascular graft composed of biodegradable scaffold seeded with autologous bone marrow-derived mononuclear cells (BMMCs) that is currently in clinical trial and developed analogous mouse models to study mechanisms of neovessel formation. We previously reported that seeded human BMMCs were rapidly lost after implantation into immunodeficient mice as host macrophages invaded the graft. As a consequence, the resulting neovessel was entirely of host cell origin. Here, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
138
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 16 publications
11
138
1
Order By: Relevance
“…20,24,25 In our study, we observed fewer a-SMA-positive cells in explanted 6-month grafts compared with 3-month grafts, suggesting physiological and not pathological remodeling in our model. In tissue-engineered vascular graft constructs, our group showed that neovessel regenerates from adjacent host blood vessels and is independent of seeded cells, 26,27 a mechanism we believe may be applicable to our current findings. Alternatively, it is possible that the transplanted dPV loses viability over time; however, further work is required to delineate the origin and fate of infiltrating host cells in TEHV recipients.…”
Section: Discussionsupporting
confidence: 70%
“…20,24,25 In our study, we observed fewer a-SMA-positive cells in explanted 6-month grafts compared with 3-month grafts, suggesting physiological and not pathological remodeling in our model. In tissue-engineered vascular graft constructs, our group showed that neovessel regenerates from adjacent host blood vessels and is independent of seeded cells, 26,27 a mechanism we believe may be applicable to our current findings. Alternatively, it is possible that the transplanted dPV loses viability over time; however, further work is required to delineate the origin and fate of infiltrating host cells in TEHV recipients.…”
Section: Discussionsupporting
confidence: 70%
“…We discovered that the vascular neotissue formation is driven by migration of the host endothelial cells and smooth muscle cells (SMCs) from the neighboring blood vessel wall through an immune-mediated process orchestrated by the seeded cells using a paracrine mechanism. 9,10 So far, our studies have focused mainly on the cellular processes involved in vascular neotissue formation, less on formation of the extracellular matrix (ECM) and the associated biomechanical factors. [7][8][9][10] There is a growing literature highlighting the importance of mechanobiological principles on vascular physiology and pathophysiology.…”
mentioning
confidence: 99%
“…9,10 So far, our studies have focused mainly on the cellular processes involved in vascular neotissue formation, less on formation of the extracellular matrix (ECM) and the associated biomechanical factors. [7][8][9][10] There is a growing literature highlighting the importance of mechanobiological principles on vascular physiology and pathophysiology. [11][12][13][14][15] For example, compliance mismatch between a vascular graft and the native vessel into which it is implanted has been demonstrated to be a critical factor, leading at times to the formation of neointimal hyperplasia and stenosis.…”
mentioning
confidence: 99%
“…85 The iPS cell sheets containing both endothelial cells and VSMCs were seeded onto a biodegradable scaffold and implanted onto the infrarenal inferior vena cava of immunodeficient mice. Ultrasonography analysis revealed that grafts persisted after by guest on May 9, 2018 http://atvb.ahajournals.org/ Downloaded from 10 weeks; however, a significant drop in iPSC number was observed on histological examination, suggesting a decline in cell survival over time.…”
Section: Tissue-engineered Blood Vesselsmentioning
confidence: 99%